PERILAKU KOMUNIKASI ETNIS SUNDA PENDATANG DALAM ADAPTASI EKONOMI, SOSIAL DAN BUDAYA PADA MAJELIS TA’LIM PAGUYUBAN BABUL AKHIRAT DI KOTA BATAM - Cindoswari, Ageng Rara (Jurnal Komunikasi Islam, 2016)
The purpose of this study : (1). To know communication behavior of Sundanese immigrant in majelis ta’lim Babul Akhirat community, (2) To know the adaptation of economic, social and cultural of Sundanese immigrant in majelis ta’lim Babul Akhirat community, (3). To know the relationship between communication behaviour Sundanese immigrant with the adaptation of economic, social, and cultural in majelis ta’lim Babul Akhirat community. This study uses a quantitative paradigm that is descriptive and correlational. There are two variables used in this research that is communication behavior and adaptation of economic, social and cultural of Sundanese immigrant in majelis ta’lim babul akhirat community. Communication behavior of ethnic Sundanese entrants focused on finding information related to the economy, social and cultural information in the context of adaptation through the majelis ta’lim Babul Akhirat community. Research was conducted on the Sundanese immigrants who are members of the majelis ta’lim Babul Akhirat community where the secretariat at Bengkong Aljabar, Batam and were selected purposively. Sampling method using census numbered 82 people. This study uses Rank Spearman statistical analysis technique that is using SPSS 19.0 for windows. The results showed (1). Communication behavior of Sundanese immigrant in majlis taklim was 43% at the high category. (2). Adaptation of the economy was 40% into so often category, social adaptation was 42% into often category, cultural adaptation was 39% into often category. (3). There is a positive and significant  relationship between Sundanese immigrant communication behavior with economic, social, and cultural adaptation in majelis ta’lim Babul Akhirat community.